THE INFLUENCE OF THE GLOBALIZATION ON THE DEVELOPED COUNTRIES IN THE EUROPEAN UNION - Tsvetkov, Tsvetomir; Ivanova, Lyubov (Revista Inclusiones, 2020)
This article examines the impact of the globalization on the economies of the developed countries of the European Union. Globalization is seen as a process and state that includes three subindicators, namely an economic, social and political globalization. From here, we consider not only the impact of globalization as a whole, but also the impact of economic, social and political globalization on EU countries. The purpose of the study is to determine what this influence is. The fixed effects least squares method and the random effects least squares method are applied to achieve the objective. The findings of the study are that the globalization has a favorable impact on the economic development of developed countries in the EU.